Mediação de conflitos no trabalho: possibilidade de restauração do diálogo no espaço de trabalho em saúde - Luciana Parisi (2016)
This research aimed to analyze processes of mediation of labor disputes in the public institution of Municipal Health Department of Belo Horizonte, which were conducted by the Human Resources and Health Education Office of the own institution, from 2012 to 2015. The analysis was directed to the process carried out in four collective bargaining, three health centers and the other in an activity management of MunicipalHealth Department of Belo Horizonte. All documentation, filed with Human Resources and Health Education Office, referring to conflicts and conducted mediation process was analyzed under different frameworks. The communication aspects of mediation followed the theoretical framework of discourse analysis and circular narrative mediation. Conflicts and its interface with the work had as a reference the transformative model of mediation and clinical work. The results showedthat mediation was successful in two analyzed and partly in a third unit. In one analyzed unit mediation did not restore the dialogue between the parties and it was possible to understand what were the factors that influenced the outcome. The determinants of the conflict analyzed were included in the four analyzed units. The results showed that even in hierarchical environments, could be used successfully to practice mediation.